The Ethics of Contentious Hard Forks in Blockchain Networks With Fixed Features - Kim, Tae Wan; Zetlin-Jones, Ariel (Frontiers in Blockchain, 2019)
An advantage of blockchain protocols is that a decentralized community of users may each update and maintain a public ledger without the need for a trusted third party. Such modifications introduce important economic and ethical considerations that we believe have been not been considered among the community of blockchain developers. We clarify the problem and provide one implementable ethical framework that such developers could use to determine which aspects should be immutable and which should not.